METODE PENGAJARAN TAHFIDZ DALAM MENGHAFAL AL-QUR’AN DI YAYASAN ISLAMIC CENTRE SUMATERA UTARA - Arlina (Inspiratif Pendidikan, 2023)
This research aims to analyze the methods used in memorizing the Qur’an at the MTs level at the Islamic Centre Foundation of North Sumatra. The focus of this study is on two things, which are the methods used in the memorization process and the process in the implementation of Qur’an memorization learning at the Islamic Centre Foundation of North Sumatra. This study used a method of curiative approach and data collection techniques obtained directly from the source directly through observation and interviews from one of the educators at the Islamic Centre Foundation of North Sumatra at the MTs level. The research results explain that the Islamic Centre Foundation of North Sumatra has two focuses: the focus of MHQ (Madrasah Hifzil Qur’an) and the focus of memorization and school, in memorizing educators at the Islamic Centre Foundation using various methods, one of which is the takrir method, the purpose of improving haphalaHe also encouraged the student against the past verse and the past letter to get stronger and stick to his head until he reached his memorized target